Global Disability Burdens of Diabetes-Related Lower-Extremity Complications in 1990 and 2016 - Zhang, Yuqi; Lazzarini, Peter A.; McPhail, Steven M.; van Netten, Jaap J.; Armstrong, David G.; Pacella, Rosana E. (Diabetes care, 2020)
No study has reported global disability burden estimates for individual diabetes-related lower-extremity complications (DRLECs). The Global Burden of Disease (GBD) study presents a robust opportunity to address this gap. GBD 2016 data, including prevalence and years lived with disability (YLDs), for the DRLECs of diabetic neuropathy, foot ulcer, and amputation with and without prosthesis were used. The GBD estimated prevalence using data from systematic reviews and DisMod-MR 2.1, a Bayesian meta-regression tool. YLDs were estimated as the product of prevalence estimates and disability weights for each DRLEC. We reported global and sex-, age-, region-, and country-specific estimates for each DRLEC for 1990 and 2016. In 2016, an estimated 131 million people (1.8% of the global population) had DRLECs. An estimated 16.8 million YLDs (2.1% global YLDs) were caused by DRLECs, including 12.9 million (95% uncertainty interval 8.30-18.8) from neuropathy only, 2.5 million (1.7-3.6) from foot ulcers, 1.1 million (0.7-1.4) from amputation without prosthesis, and 0.4 million (0.3-0.5) from amputation with prosthesis. Age-standardized YLD rates of all DRLECs increased by between 14.6% and 31.0% from 1990 estimates. Male-to-female YLD ratios ranged from 0.96 for neuropathy only to 1.93 for foot ulcers. The 50- to 69-year-old age-group accounted for 47.8% of all YLDs from DRLECs. These first-ever global estimates suggest that DRLECs are a large and growing contributor to the disability burden worldwide and disproportionately affect males and middle- to older-aged populations. These findings should facilitate policy makers worldwide to target strategies at populations disproportionately affected by DRLECs.